2017
DOI: 10.1007/s00401-017-1714-x
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious ABCA7 mutations and transcript rescue mechanisms in early onset Alzheimer’s disease

Abstract: Premature termination codon (PTC) mutations in the ATP-Binding Cassette, Sub-Family A, Member 7 gene (ABCA7) have recently been identified as intermediate-to-high penetrant risk factor for late-onset Alzheimer’s disease (LOAD). High variability, however, is observed in downstream ABCA7 mRNA and protein expression, disease penetrance, and onset age, indicative of unknown modifying factors. Here, we investigated the prevalence and disease penetrance of ABCA7 PTC mutations in a large early onset AD (EOAD)—control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 53 publications
2
93
1
Order By: Relevance
“…The variants in TREM2 have been reported in a previous analysis of this dataset (Song et al., ). Likewise, deleterious mutations in ABCA7 are known to be risk factors for both early‐ and late‐onset AD (De Roeck et al., ). The variants in SORL1 at 11:121348842 (rs140888526), 11:121421313 (rs148430425), and 11:121421361 (rs146438170) have not previously been implicated in LOAD susceptibility and although the gene‐based SLP of 4.42 suggests that overall there is an excess of functionally significant variants among cases, the numbers are too small to draw any definitive conclusions about any of these variants individually.…”
Section: Resultsmentioning
confidence: 99%
“…The variants in TREM2 have been reported in a previous analysis of this dataset (Song et al., ). Likewise, deleterious mutations in ABCA7 are known to be risk factors for both early‐ and late‐onset AD (De Roeck et al., ). The variants in SORL1 at 11:121348842 (rs140888526), 11:121421313 (rs148430425), and 11:121421361 (rs146438170) have not previously been implicated in LOAD susceptibility and although the gene‐based SLP of 4.42 suggests that overall there is an excess of functionally significant variants among cases, the numbers are too small to draw any definitive conclusions about any of these variants individually.…”
Section: Resultsmentioning
confidence: 99%
“…ABCA1, ABCA7, and ABCB1 (also known as P-glycoprotein) are members of the ABC family of transporters that are important for the clearance of Aβ, and hence, their loss of function results in the accumulation of plaques in the brain. ABCA7 is particularly relevant, as recent studies have shown that loss-of-function polymorphisms at its gene increase the risk for late- [ 75 ] and early-onset AD [ 76 ]. These transporters use the binding and hydrolysis of ATP to power the translocation of several substrates ranging from ions to macromolecules across membranes.…”
Section: The Immune-related Clearance Mechanisms For Aβmentioning
confidence: 99%
“…The variants in TREM2 have been reported in a previous analysis of this dataset (Song et al, 2017). Likewise, deleterious mutations in ABCA7 are known to be risk factors for both early and late onset Alzheimer's disease (De Roeck et al, 2017). The variants in SORL1 at 11:121348842 (rs140888526), 11:121421313 (rs148430425) and 11:121421361 (rs146438170) have not previously been implicated in LOAD susceptibility and although the gene-based SLP of 4.42 suggests that overall there is an excess of functionally significant variants among cases the numbers are too small to draw any definitive conclusions about any of these variants individually.…”
Section: Resultsmentioning
confidence: 99%